Appropriate use criteria for lumbar puncture and cerebrospinal fluid testing in the diagnosis of Alzheimer's disease. Issue 11 (10th October 2018) - Shaw, Leslie M.; Arias, Jalayne; Blennow, Kaj; Galasko, Douglas; Molinuevo, Jose Luis; Salloway, Stephen; Schindler, Suzanne; Carrillo, Maria C.; Hendrix, James A.; Ross, April; Illes, Judit; Ramus, Courtney; et al.
Abstract: Introduction: The Alzheimer's Association convened a multidisciplinary workgroup to develop appropriate use criteria to guide the safe and optimal use of the lumbar puncture procedure and cerebrospinal fluid (CSF) testing for Alzheimer's disease pathology detection in the diagnostic process. Methods: The workgroup, experienced in the ethical use of lumbar puncture and CSF analysis, developed key research questions to guide the systematic review of the evidence and developed clinical indications commonly encountered in clinical practice based on key patient groups in whom the use of lumbar puncture and CSF may be considered as part of the diagnostic process. Based on their expertise and interpretation of the evidence from systematic review, members rated each indication as appropriate or inappropriate. Results: The workgroup finalized 14 indications, rating 6 appropriate and 8 inappropriate. Discussion: In anticipation of the emergence of more reliable CSF analysis platforms, the manuscript offers important guidance to health‐care practitioners and suggestions for implementation and future research.